Research Progress of MicroRNA in the Diagnosis and Treatment of Age-Related Macular Degeneration - sun lei (Pacific International Journal, 2026)
Age-related macular degeneration (AMD) is a disease affected by environmental and genetic factors and is one of the common causes of visual impairment in the elderly. impairment in the elderly. MicroRNAs (miRNAs) are a type of abundant endogenous, single-stranded, non-coding RNA molecules, whose abnormal expression in AMD is related to inflammation, oxidative stress, and the effects of the disease. expression in AMD is related to inflammation, oxidative stress, and cell apoptosis. Identifying specific miRNA biomarkers for AMD will provide valuable tools for early intervention. Identifying specific miRNA biomarkers for AMD will provide valuable tools for early intervention. Strategies for regulating miRNA therapy in AMD may also become a new option.